Selection of design approach for designing spread foundations in our region according to Eurocode 7 - Papic, Jovan; Prolovic, Verka; Dimitrievski, Ljupcho (My University, 2014)
The existing civil engineering standards for designing are to be replaced with a set of Eurocodes. Eurocode 7 is related to a geotechnical design, but its imple¬men¬ta¬tion is difficult, due to different geological, geographical and climate conditions which lead to development of different local designing traditions all over Europe. In order to overcome them, Eurocode 7 offers three design approaches and sets of partial factors to be used within. After accepting it, each country has to declare on the selection of design approach according to which designing is going to be performed and to define appropriate partial factors. This paper presents metho¬do¬lo¬gy for selection of appropriate design approach for spread foundations in our region where the process of introduction of Eurocodes is still active. The method based on keeping up with the similar designing procedure may also be used for other geotechnical structures.
Keywords: Eurocode 7, geotechnical design, design approach, spread foundations